Lower Levels of Vitamin D Are Associated with Higher Vasoactive–Inotropic Scores in Major Cardiac Surgery - Adrian Stef; Constantin Bodolea; Simona Sorana Cainap; Monica Muntean; Aurelia Georgeta Solomonean; Nadina Tintiuc; Razvan Olimpiu Mada; Gabriel Cismaru (Life, 2024)
Background: The vasoactive–inotropic score (VIS) predicts unfavorable outcomes after cardiac surgery in both children and adults. In our adult population, we investigated whether preoperative levels of vitamin D can predict the VIS and whether both vitamin D and the VIS can predict adverse outcomes following major heart surgery. Methods: Between 1 October 2021 and 28 February 2022, 300 patients underwent major cardiac surgery at our institution. Eighty-three of them had their 25-OH vitamin D levels measured before surgery. For this cohort, we calculated the VIS based on doses of vasoactive and inotropic medications administered post-surgery. Utilizing receiver operating curves, the predictive accuracy of vitamin D levels and the VIS in predicting acute kidney injury was assessed. Results: The median age of the cohort was 66 (IQR 61–71) years, with 59% being male and a median BMI of 28.4 (IQR 25.2–31.6). The most common procedures were aortic valve replacement, mitral valve replacement, coronary artery bypass grafting, aortic valve and ascending aorta repair, and ASD correction. There was a significant difference in the postoperative VIS between patients with vitamin D deficiency, i.e., <20 ng/mL, and patients with vitamin D values > 20 ng/mL (3.5 vs. 1.3 p < 0.04). We also found a significant correlation between the VIS and the days of hospitalization (r = 0.335; p = 0.002), the days of stay in the intensive care unit (r = 0.547; p < 0.00001), and the mechanical ventilation time (r = 0.327; p = 0.025). Both vitamin D levels and the VIS predicted postoperative acute kidney injury (p < 0.05). Conclusions: Vitamin D deficiency is correlated with the VIS in adults undergoing major cardiac surgery. Both vitamin D levels and the VIS can predict unfavorable postoperative outcomes.